The Effect of Resistance Exercise on Memory and Neurotrophic Factors in Sedentary Students - Mehdi Shahbazi; Aboalfazl Shayan; Ali Samadi; Zahra Nemati (University of Tehran, 2015)
There are evidences in both animal and human studies which show that exercise has beneficial effects on the central nervous system and cognition. So, the aim of this study was to investigate the effect of resistance exercise on memory and probable mechanisms of this effect (i.e. neurotrophic factors) in sedentary students. 30 sedentary students (mean age, 23.8±1.6 yr) were randomly divided into two groups: control and resistance. After blood sampling and memory test, they continued their exercises for 5 weeks based on the resistance training protocol. In the end, at least 48 hours after the last training session, the memory test and blood samples were collected in order to eliminate the temporary effects of exercises. For analysis of the data, Covariance test and Pearson correlation coefficient were used (P≥0.05). Results showed that resistance exercises significantly increased memory score (P<0.05). Although BDNF significantly increased after the exercises, the exercises did not influence the expression of any neurotrophic factors (P˂0.05). Furthermore, there was no significant correlation between variations of memory scores and variations of expression of neurotrophic factors (P˂0.05). The findings indicated that exercise can improve memory.